2006
DOI: 10.1017/s0950268806006303
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and serotype distribution of Streptococcus pneumoniae isolated from patients with community-acquired pneumonia and molecular analysis of multidrug-resistant serotype 19F and 23F strains in Japan

Abstract: A nationwide study was undertaken to determine the susceptibility to penicillin and serotypes of Streptococcus pneumoniae in Japan. S. pneumoniae was isolated from 114 adult patients with community-acquired pneumonia over 22 months at 20 hospitals and medical centres in different regions in Japan. All but five isolates were from sputum. Forty-eight isolates (42·1%) were susceptible, 40 (35·1%) showed intermediate resistance (MIC, 0·12–1·0 μg/ml) and 26 (22·8%) were resistant (MIC, [ges ]2·0 μg/ml) to penic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…In this study, we found that 72.6% and 83.3% of all strains were not susceptible to penicillin and macrolides, respectively, numbers that were very close to the findings of previous studies (14,30). One possible cause of the increase in drug resistance is long-term antimicrobial therapy (15).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that 72.6% and 83.3% of all strains were not susceptible to penicillin and macrolides, respectively, numbers that were very close to the findings of previous studies (14,30). One possible cause of the increase in drug resistance is long-term antimicrobial therapy (15).…”
Section: Discussionsupporting
confidence: 90%
“…Using 5 major databases, we comprehensively conducted systematic literature survey to identify studies that reported on the serotype distribution of adult pneumococcal pneumonia. In our pooled data analysis of the 4 studies (1,(17)(18)(19), the proportion of PCV7-covered serotypes decreased significantly and the proportions of serotypes of PCV13-PCV7, PPV23-PCV7, PPV23-PCV13, and non-VTs increased significantly. In summary, the decrease of the proportion of PCV7-covered serotype led to the increase of the proportion of non-PCV7-covered strains.…”
Section: Discussionmentioning
confidence: 73%
“…All of the studies were performed in the pre-PCV13 period. The study designs could be categorized into case series of pneumococcal LRTI (15,16), prospective surveillance of pneumococcal LRTI or IPD cases (1,(17)(18)(19)(20), and laboratory-based pneumococcal strain surveillance (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). One of the prospective surveillance studies of the LRTI referred to the Japanese Respiratory Society (JRS) guidelines for the management of community-acquired pneumonia in adults (36) as diagnostic criteria for LRTI (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an increasing worldwide problem of drug resistance among respiratory pathogens, notably S. pneumoniae which has shown increasing levels of penicillin and macrolide resistance (10)(11)(12)(13) (1,6,7). Resistance to macrolides among strains of S. pneumoniae is caused by two principal mechanisms: 1) methylation of a ribosomal binding site, which is encoded by the ermB gene; and 2) active drug efflux via a cell membrane protein transporters, which is encoded by the mefA gene (14).…”
Section: Community-acquired Pneumonia (Cap) Is a Common And Potentialmentioning
confidence: 99%